Forever - Stiefvater, Maggie 1981- (New York Scholastic Press, 2011)
A human girl and her werewolf boyfriend must fight for their love as death comes closing in
1
Keywords: Human-animal relationships -- Fiction; Love -- Fiction; Metamorphosis -- Fiction; Supernatural -- Fiction; Wolves -- Fiction